Rational fabrication of low carbon foot-print electrode materials for lithium-ion batteries from electric arc furnace dust via integrated hydrometallurgical process - Karahan, Billur Deniz (Elsevier Ltd, 2023)
Transforming industrial waste into high-value-added products represents a new avenue in the field of material science. This paper puts forward a comprehensive example for future works which target fabricating low-carbon footprint electrodes for rechargeable batteries. Within this scope, first time in the open literature, an integrated hydrometallurgical process has been designed to fabricate metal oxide powders of different properties from electric arc furnace (EAF) dust. Leaching, cementation, distillation, chemical precipitation, and calcination are used to produce powders rich in zinc oxide (Sample 1), ferrite (Sample 2), and nanocomposite (Sample 3) from the electric arc furnace flue dust. While sample 1 (zinc oxide with 97.8% purity) may be used in optics and other engineering applications, sample 2 (rich in zinc ferrite) and sample 3 (made of nanocomposites) that are recovered from the EAF dust may be utilized as electrode active material in lithium-ion batteries: Sample 2 and Sample 3 retain 43% and 50% of their capacities after 125th cycle, respectively. To further improve the cycle performance of Sample 2, the powder rich in ferrite is mixed with nickel salt, then heat treated. The latter performs 65% capacity retention after 125th cycle. The fact that every fabricated electrode achieves 125 cycles with success demonstrates the viability of the proposed technique; thus, various procedures may be developed to further elaborate the use of various industrial wastes in electrode fabrication.
Keywords: Green Materials; Leaching; Lithium-Ion Batteries; Selective Metal Recovery; Zinc Ferrite